Aquifers Shared Between Mexico and the United States: Management Perspectives and Their Transboundary Nature. Issue 4 (10th May 2017) - Sanchez, Rosario; Eckstein, Gabriel
Abstract: Totally 36 aquifers have been identified along the Mexico‐U.S. border. Of these, only 16 have adequate data to provide a reasonable level of confidence to categorize them as transboundary. Limited and/or contrasting data over the other aquifers in the region reflects the void in transboundary groundwater management and assessment mechanisms throughout much of the Mexico‐U.S. border. This paper identifies management mechanisms, structures, and institutional prioritization related to transboundary aquifers shared between Mexico and the United States. It also evaluates the differences in the transboundary nature of these aquifers, and how their combined hydrological and geographical considerations interrelate with local and regional social, economic, political, and even scale dimensions to create complex management challenges. Abstract : Article impact statement : Transboundary groundwater management is basically absent on the border between Mexico and the United States.